A community-based early childhood development center platform promoting diversified diets and food production increases the mean probability of adequacy of intake of preschoolers in Malawi: A cluster randomized trial - Gelli, Aulo; Nguyen, Phuong Hong; Santacroce, Marco; Twalibu, Aisha; Margolies, Amy; Katundu, Mangani (American Society for Nutrition, 2020)
Background: Young children in Malawi consume low-quality diets lacking micronutrients critical for their development. Objective: To evaluate the impact of an agriculture and nutrition behavior change communication (BCC) intervention implemented through community-based childcare centers on the nutrient adequacy of diets of children living in food-insecure settings in Malawi.